The ostracod fauna of the Plio-Pleistocene Monte Mario succession (Roma, Italy) - FARANDA C; GLIOZZI, Elsa (2008)
The marine ostracods collected during a recent re-sampling of the “classical” Plio-Pleistocene Monte Mario succession (Roma, Latium) are here listed and, in some cases, some species have been taxonomically reviewed. Ostracod faunas come from the late Zanclean Monte Vaticano Fm. and from the early Calabrian (Santernian p.p.) Monte Mario Fm. For each species an updated stratigraphical distribution is reported. Five new species have been arisen: Callistocythere dubia nov. sp., Ionicythere planocostata nov. sp., Aurila (Aurila) diversofoveolata nov. sp., Eucytherura vaticana nov. sp. and Semicytherura marialuisae nov. sp. Except for Callistocythere dubia nov. sp., collected also in the Gelasian of Kos (Greece), Calabrian (Emilian) of Vrica (Calabria) and in the recent sediments of Golfo di Saline (NE Sardinia) and for Semicytherura marialuisae nov. sp., collected in the Calabrian (Santernian- Emilian) of Vrica (Calabria), the other new species are exclusive of the Monte Mario succession. Four new “northern guest” ostracods for the early Calabrian (Santernian) of the Mediterranean area (Bythocythere zetlandica, Cytheropteron (Cytheropteron) depressum, Paradoxostoma ensiforme and Paradoxostoma abbreviatum) have been collected in the Monte Mario Fm., in the same levels where literature reports the presence of the “northern guest” molluscs Arctica islandica, Cochlodesma praetenue and Buccinum humphreysianum, confirming the cold climatic oscillation during which the Sabbie grigie ad Arctica islandica deposited. Moreover, the already known “warm” Calabrian (Santernian) guest Mediocytherideis (Sylvestra) virgula has been collected in the upper portion of the Monte Mario succession. These findings, together with the temporal constrain of the Monte Mario Fm. to the early Calabrian (Santernian p.p., owing to the absence of Calcidyscus macintyrei and large Gephyrocapsa), allowed to tentatively refer the deposition of the Monte Mario Fm. between the cold OIS 58 and the warm OIS 55.